Identifikasi Ganoderma Kelapa Sawit Sebelum dan Sesudah Pembumbunan di Kebun TIU PTPN IV Regional II - Sultan Rizki Subhandri Chaniago; Sulthon Parinduri (Universitas Medan Area, 2026)
The purpose of this study was to identify basal stem rot disease in oil palm plants caused by Ganoderma boninense and to evaluate the effectiveness of the hilling method at the Tanah Itam Ulu Plantation of PTPN IV Regional II. This is due to the fact that oil palm is a strategic commodity that is highly susceptible to pathogen attacks, especially Ganoderma, which causes decreased productivity and plant mortality. The method used was descriptive analysis based on tree inventory data in blocks (09R and 09S) without hilling and with hilling (09X and 09Y) during the period 2020–2025. This data was obtained through observation, interviews, and field censuses. The results showed that the overall plant population in the blocks decreased annually. This decline was caused by various factors, including disease, plant age, and environmental conditions. However, the rate of decline in the blocks treated with hilling was lower than in the untreated blocks. Hilling has been shown to improve plant stability by forming new roots and increasing the efficiency of water and nutrient absorption. However, this method has not been able to completely halt the disease's progression. To increase the effectiveness of Ganoderma control on a sustainable basis, hilling is recommended as part of an integrated control approach combined with biological agents, orchard sanitation, and early detection.